PENGARUH PENYALURAN KREDIT DAN KREDIT BERMASALAH TERHADAP PROFITABILITAS PERUSAHAAN PASCA PANDEMI COVID-19 (Studi Pada PT. BPR Chandra Muktiartha) - Khasanah, Mutiara Hening Uswatun; Giyartiningrum, Eko (Journal Competency of Business, 2024)
Financial management is very important in managing a company's funds not only in obtaining funds, financial management also plays a role in determining the appropriate amount of assets from investments in various assets and selecting sources of funds to spend these assets. The same is true in the banking world. This type of research is descriptive quantitative. Descriptive research is data collection to test hypotheses or answer questions about the latest status of research subjects. The definition of quantitative itself is research that emphasizes theory testing through measuring research variables with numbers and analyzing data with statistical procedures PT BPR Chandra Muktiartha is one of the companies. The results of the analysis concluded that there was insufficient evidence to support the significant influence of the variables of lending (LDR) and non-performing loans (NPL) on the company's Return on Assets (ROA). Therefore, these results suggest that other factors may be more dominant in influencing the company's ROA that are not considered in this model